The optimisation of throwing movements with evolutionary algorithms on the basis of multibody systems - Bächle, F. (International Journal of Computer Science in Sport, 2002)
The motion of kinetic chains in throwing events is an object of biomechanics research. Statements about optimal movements are made on the basis of velocity-time-diagrams (OGIOLDA 1993; KOLLATH 1996; BEST/BARTLETT/MORRISS 1993; KROONENBERG 1991). However, these statements are inconsistent. The use of evolutionary algorithms points an alternative of gaining insight into this complex object of research (PERL/LAMES/GLITSCH 2002; SPRIGINGS/NEAL 2000). This contribution deals with the optimisation of a three chain kinetic link in a throwing movement (throw-in in soccer) on the basis of multi-body systems by using an evolution strategy (ES). The optimisation is made by using an ES coded in Matlab (POLAND 2002) in connection with Simulink and a multi-body simulation software. The multi-body model is composed of four rigid bodies (trunk, upper arm, forearm/hand). They are connected with joints (hip, shoulder, elbow). The motion of the segments towards each other is realized with "massless motors". The maximum tangential velocity of the distal segment (hand) is the fitness function for the ESCode. This contribution shows that the use of evolution strategies is one way of solving the problem of optimisation of complex sporting movements (of non-linear dynamic systems).